Acute appendicitis in pregnancy: an integrative review (Research, Society and Development, 2023)
To analyze the methods used to diagnose and treat acute appendicitis in pregnant patients, also aiming to differentiate these methods when performed on non-pregnant patients. This article is an integrative literature review. The databases of scientific articles were used to perform the searches: Us National Library Of Medicine (PUBMED) and Scientific Electronic Library Online (SCIELO). The terms were used to meet the theme: “Appendicitis” AND “Pregnancy” AND “Laparoscopy”. The time frame includes articles published between 1995 and 2022. Acute appendicitis in pregnancy is the most common cause of non-obstetric abdominal disease that determines the need for emergency surgery. In addition, acute appendicitis in pregnant women is difficult to diagnose due to the anatomical and physiological changes resulting from pregnancy, such as displacement of the appendix due to uterine growth. In case of acute appendicitis in women, laparoscopic surgery is the best method to be used, since it provides advantages in the postoperative period that open surgery does not provide. Acute appendicitis in pregnant women, even with low mortality nowadays, needs to be diagnosed quickly, since appendix perforation can increase mortality and put mother and fetus at risk.